(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Many successful technological firms today are built on pair programming. Pair programming is a technique for inspecting code as it is written; it is also a real-time problem solving and quality assurance activity. Two people, a driver, and an observer, use a single keyboard and mouse to program all production code on a single system in pair programming. The driver is responsible for implementing the current module at hand. The navigator is an online reviewer tasked with ensuring the quality of the code. We were unable to determine the true impact of pair programming on software quality assurance because many pair programming studies were not conducted as described in Extreme programming and the empirical evidence of pair programming is contradictory. We investigated the effect of dynamic pairs (pair rotation) on real-time software quality assurance in terms of program accuracy and code quality in this study. Our research indicates that pair programming with frequent pair rotation produced a higher quality software system and code in less time than pair programming without pair rotation, and produced higher quality software and code than individual programming in approximately the same amount of software development time.